Pembelajaran Digital Pedagogi melalui Edutainment Berbasis Game: Model Pembelajaran bagi Anak Asuh Panti Asuhan Muhammadiyah Kabupaten Pamekasan - Abdul Ghofur; Deddy Wahyudi; Muhammad Hadiatur Rahman; Itaanis Tianah; Shinta Oktafiana; Tholiatur Rizkiyah (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
The Muhammadiyah Orphanage in Pamekasan faces major challenges in developing life skills and digital education for its children due to limited facilities, teaching staff, and conventional learning methods. To address these issues, an edutainment-based approach and digital pedagogy intervention were implemented to enhance learning quality, motivation, and preparedness for future social and technological challenges. The activities included workshops and training on Digital Pedagogy and Edutainment learning materials, as well as simulations and role-plays using a Game-Based Learning approach, followed by evaluations and participant plan presentations. The program significantly improved the wards’ digital literacy, particularly in personal security (online safety), digital ethics (cyber ethics), gadget usage, and information management, with the average score rising from 2.84 to 4.10 on a 5-point scale, surpassing the target of 75% of participants in the “good” category. Beyond cognitive aspects, the program also boosted motivation, engagement, communication, problem-solving, and independence. Caregiver training was also provided to ensure program sustainability. It is recommended that the orphanage integrate the Game-Based Learning Digital Safety module into its non-formal curriculum, enhance caregiver capacity through advanced training, and improve IT infrastructure.